Remains of pillars at the entrance of the Someshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
These are the remains of pillars at the east-facing entrance of the Someshwar Mahadev Temple. The two broken pillar bases must have formed the torana (decorative arch) as an entrance gateway to the complex. The complex had at least two such toranas, one to the east of the temple and another to the north.